2020
DOI: 10.1177/2192568220960075
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Deformity Surgery in Pediatric Patients With Cerebral Palsy: A National-Level Analysis of Inpatient and Postdischarge Outcomes

Abstract: Study Design: Retrospective cohort. Objective: To provide a national-level assessment of the short-term outcomes after spinal deformity surgery in pediatric patients with cerebral palsy. Methods: A national, prospectively collected database was queried to identify pediatric (≤18 years) patients with cerebral palsy, who underwent spinal fusion surgery from 2012 to 2017. Separate multivariate analyses were performed for the primary outcomes of interest including extended length of stay (>75th percentile, >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Major complication rates can be as high as 40% following surgery for scoliosis in patients with CP, and the reoperation rate is around 14%. [5][6][7] It is critical to understand patient characteristics and specific radiographic findings that place these patients at greater risk for morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Major complication rates can be as high as 40% following surgery for scoliosis in patients with CP, and the reoperation rate is around 14%. [5][6][7] It is critical to understand patient characteristics and specific radiographic findings that place these patients at greater risk for morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these benefits to children with CP, the decision to undergo spinal fusion surgery is challenging due to the heightened risk of postoperative complications seen in this complex patient population. Past literature has shown that postoperative complications are common in the patient population with CP 14 . This is often attributed to the overall complexity of performing spinal surgery on patients with CP who typically present with additional comorbidities and more pronounced spinal deformities 14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, consideration of nutrition status decreases the postoperative complication and the incidence of surgical site infection in neuromuscular scoliosis decreased significantly (16.1% vs. 4.4%) after the implementation of the strategies mentioned in the 2013 Best Practice Guideline. [37][38][39] Postoperative fever is a frequent complication after surgery. Yousef et al 40 reviewed 76 patients who had undergone scoliosis surgery and 49 patients (64.5%) who developed postoperative fever with a temperature of > 38°C.…”
Section: A C C E P T E D a R T I C L E 10mentioning
confidence: 99%
“…Deep surgical site infections were more common in neuromuscular scoliosis (10.0%) than in adolescent idiopathic scoliosis, kyphosis (2.7%), or genetic and syndromic scoliosis (4.2%). However, consideration of nutrition status decreases the postoperative complication and the incidence of surgical site infection in neuromuscular scoliosis decreased significantly (16.1% vs. 4.4%) after the implementation of the strategies mentioned in the 2013 Best Practice Guideline [ 38 - 40 ]. Postoperative fever is a frequent complication after surgery.…”
Section: Outcomes and Complications After Surgerymentioning
confidence: 99%